Floating bioadhesive drug delivery system using novel effervescent agents - Belgamwar, V S; Surana, S J (Asian Journal of Pharmaceutics (AJP), 2014)
Oral sustained release gastroretentive dosage forms offer many advantages for drugs having absorption from the upper gastrointestinal tract and improve the bioavailability of medications that are characterized by the narrow absorption window. A new gastroretentive sustained release delivery system using the novel effervescent system was developed with floating, swellable, and bioadhesive properties. Various release retarding polymers like psyllium husk, HPMC K15M, and a swelling agent crosspovidone in different combinations were tried and optimized to get the release profile for 12 hours. TheÂ  formulations were evaluated for physicochemical characteristics, in vitro drug release profile, swelling characteristics, floating capacity, and in vitro bioadhesive property. in vitro drug release followed the Higuchi kinetics and the release mechanism was found to be of a non-Fickian type. The swelling properties were increased with increasing crosspovidone concentration and contributed to the drug release from the tablet matrix. In this study, an attempt has been made to explore novel effervescent agents such as citroglycine and disodium glycine carbonate for achieving the desired floating time.